Crowdfunding Conservation Science: Tracing the Participatory Dynamics of Native Parrot Genome Sequencing. (May 2022) - Addison, Courtney; Stevens, Hallam
Who gets to practice and participate in science? Research teams in Puerto Rico and New Zealand have each sequenced the genomes of parrot populations native to these locales: the iguaca and kākāpō, respectively. In both cases, crowdfunding and social media were instrumental in garnering public interest and funding. These forms of Internet-mediated participation impacted how conservation science was practiced in these cases and shaped emergent social roles and relations. As citizens "follow, " fund, and "like" the labor of conservation, they create new relational possibilities for and with science. For example, the researchers became newly engaged and engaging by narrating and displaying the parrots via an Internet-inflected aesthetic. The visibility of online modalities shifted accountabilities as researchers considered whom this crowdfunded work answered to and how to communicate their progress and results. The affordances of the Internet allowed researchers from the peripheries of the scientific establishment to produce genomic knowledge for globally dispersed audiences. The convergence of genomic and Internet technology here shaped scientific practice by facilitating new modes of participation—for laypeople in science but also for scientists in society.